Teacher Emotional Intelligence in Motivating Student Learning at SMPN 24 Batanghari Jambi - Abduil Mutalib; Moatti Dylan (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2021)
This article explains how emotional intelligence an educator's energy is able to give the maximal contribution in motivating to learn the student. The teacher is a professional educator with the special duty of educating, teaching, guiding, instructing, training, assessing and evaluating educated competitors [at the] band of formal education. intelligence a teacher in so many areas is needed, one of them is emotional intelligence. Motivate the part of internal factors and represent psychology in its relation/link with the school activity. Educator energy as a human resource representing a big investment asset which if exploited will become a very valuable capital in reaching the intention of an educational institute beside another capital source. Educator energy as a special component and handle of calyx education plays a very significant role in educational efficacy. For the reason, besides the standard interest which must be owned by a teacher, emotional intelligence plays a role which is significant enough in forming the characteristics of a teacher remembering with the emotional intelligence, a teacher will be able to control his emotions and also be able to play the role it's social with the teacher humanity, students, and also societ